Radio and photo luminescence of Dy3+ doped lithium fluorophosphate scintillating glass. (August 2021) - Rajagukguk, J.; Sarumaha, C.S.; Chanthima, N.; Wantana, N.; Kothan, S.; Wongdamnern, N.; Kaewkhao, J.
Abstract: The paper was reported on the spectrum results of Dy 3+ (1.0 mol%) ions-doped Li2 O–AlF3 –NaF–KF–P2 O5 (LANKPD) glass. The absorption spectrum was investigated in the UV–Vis–NIR region from 300 to 2000 nm. Judd-Ofelt parameters, Ωλ ( λ  = 2, 4, 6) has been evaluated from absorption spectrum. Several J-O parameters: oscillator strength, radiative transition probability, stimulated emission cross section and branching ratio also observed. The Ω2  > Ω4  > Ω6 trend of J-O parameters for glass sample exhibits the good quality of host glass for using as an optical device application. The highest excitation spectrum showed at 351 nm for transition 6 H5/2  →  6 P7/2 . The emission spectrum showed two major peaks corresponding to 483 nm blue emission ( 4 F9/2  →  6 H15/2 ) and 572 nm yellow emission ( 4 F9/2  →  6 H13/2 ). Moreover, the radioluminescence spectrum was measured and compared with the BGO scintillation crystal. Highlights: Dy 3+ doped Li2 O–AlF3 –NaF–KF–P2 O5 (LANKPD) glass was prepared. Ωλ ( λ  = 2, 4, 6) has been evaluated and found Ω2  > Ω4  > Ω6 . J-O parameters exhibits for using as an optical device. The high emission of 483 nm ( 4 F9/2 . →  6 H15/2 ) and 572 nm ( 4 F9/2  →  6 H13/2 ) were observed. RL was measured and compared with the BGO scintillation crystal.